Immunological Studies on Viral Polypeptide Synthesis in Cells Replicating Murine Sarcoma-Leukemia Virus - Shanmugam, G. (1972)
Antibodies to disrupted murine sarcoma-leukemia virus (MSV[MLV]) were used to study the synthesis of viral polypeptides in the transformed, virus-producing rat cell line 78A1. When cultures were labeled for 10 min with radioactive amino acids, about 9% of the total labeled proteins were precipitated with antiserum against purified MSV(MLV), and 3 to 4% were precipitated with the same antiserum after it had been absorbed with an extract from uninfected rat cells. The difference is due to the presence in the unabsorbed antiserum of antibodies to cellular proteins that are present in purified virus preparations. Intracellular viral proteins labeled with radioactive amino acids were isolated by immunoprecipitation and analyzed by electrophoresis in sodium dodecyl sulfate-polyacrylamide gels. The mobilities of intracellular viral polypeptides were identical to those of the purified virion. However, labeled polypeptides having electrophoretic mobilities lower than that of the major virion polypeptide, the group-specific antigen of molecular weight 31,000, were present in higher proportion in the total cell extract and in the membrane fraction than in the virion. These polypeptides appear to be of cellular origin for they were present only in minute amounts in the immunoprecipitates obtained with the absorbed serum. After a 10-min labeling period, radioactive proteins were assembled into extracellular virions rapidly for the first 4 hr followed by a slower rate. More than 2% of the total proteins of the cell labeled in a 10-min pulse were assembled into virions at the completion of a 24-hr chase. The high-molecular-weight polypeptides with the same mobilities as those detected in the immunoprecipitate of intracellular proteins were found in virions released from cells after a 10-min pulse. A larger proportion of these high-molecular-weight proteins was detected in virions released after short chase periods (30-120 min) than after longer chase periods (6-24 hr). Two possible interpretations of these data are that the high-molecular-weight cell-derived polypeptides (i) have a turnover rate higher than that of the major virion polypeptides or (ii) are cleaved proteolytically from the virions during long incubation in the culture media.